Political and Armed Struggle for Jerusalem, 1947–1948 - Kalmár, Zoltán (Acta Scientiarum Socialium, 2015)
Political and Armed Struggle for Jerusalem, 1947–1948 Jerusalem is in the crosshairs of political conflicts between Palestinians and Israelis. British Mandate administration in Palestine descended into chaos in 1948. Neither in Palestine in general, nor in Jerusalem could the United Nations enforce the UN General Assembly Partition Resolution 181 (II) of 29 November 1947. The present essay analyses the wave of violence that surged in Palestine in the wake of the United Nations resolution dividing the territory, and examines the battle for Jerusalem in 1948.
Keywords: Middle East; Jerusalem; UN General Assembly Resolution 181 (II); first Arab-Israeli war